Are There Multiple Motivators for Helping Behavior in Rats? - Silva, Phietica R. R.; Silva, Regina H.; Lima, Ramón Hypolito; Meurer, Ywlliane S.; Ceppi, Bruno; Yamamoto, Maria Emilia (Frontiers in Psychology, 2020)
Empathy is the ability to: (a) be affected by and share the emotional state of another; (b) assess the reasons for the other’s state; and (c) identify with the other, adopting their perspective. This phenomenon has been shown for several species and is proposed as a motivator for prosocial behavior. The experimental study of this feature in laboratory rodents is a more viable alternative in comparison to wild animals. A recent report showed that rats opened a door to free their cage mate from a restrain box. Although this behavior has been suggested to be motivated by empathy, this fact has been questioned by several studies that proposed other motivators for the releasing behavior. In the present study, we use an adaptation of the protocol of releasing behavior to investigate aspects of empathy and pro-sociality such as familiarity and reciprocity. In addition, we addressed some potential motivational factors that could influence this behavior. The main results showed that: (1) rats opened the restrain box to free the co-specific most of the time; (2) direct reciprocity or past experience of the restricted situation did not improve releasing performance, probably due to a ceiling effect; (3) after a series of trials in the presence of a restricted co-specific, the free rat continues to open the restrain box even if it is empty; (4) in general, the opening performance improves across trials and phases, resembling learning curves; (5) if the first series of trials occurs with the empty box, the opening behavior do not occur, and is modest in subsequent trials with a trapped animal; (6) exploratory drive towards the restrain box and desire for social contact do not seem to function as key motivators for releasing behavior. In conclusion, our findings do not support that the opening behavior is exclusively related to empathic motivation. While multiple factors might be involved, our study suggest that task learning triggered (and possibly reinforced) by the presence of the restricted rat can function as a motivator. Further investigations are required to fully understand the mechanisms and motivation factors guiding the releasing behavior.